COUNTERFEITING DRUGS AND LOGISTIC CYCLE OF DRUG SUPPLY IN LIBYAN MARKET. - LAILA M.KAFU, (International Journal of Pharma and Bio Sciences, 2014)
Libya is one of the largest Arab countries. It lies in northern Africa along the south coast of the Mediterranean Sea. Libya extent from the Mediterranean coast into the vast Sahara and ranks fourth in size among the countries of Africa, it covers about 678,400 square miles (1.759.540 square Kilometers). Libya with many developing countries suffers from the lack of documented national drug policy which makes many problems through the health services like entrance of counterfeiting drugs and sundries like for example sutures. Libya is bordered by Tunisia and Algeria, on the west, Niger and Chad on the south Sudan and Egypt on the east. All borders are opened rounding the country so the problem of counterfeit drugs increasing. The problem of counterfeit medicines was first addressed at the international level in 1985’s. It has been introduced into the Libyan private market at the beginning of year 2003 then it becomes a big issue, the situation of this problem has come on scene, during that time many items of medicines were introduced illegally, and samples of such medicines were noted tested by the Pharmaceutical control laboratories, and work spread in the black market in this field which is well known as a very sensitive field.